Successful management of severe acute liver disease related with adult-onset Still’s disease in a pregnant patient - Özgür HARMANCI; Taylan KAV; Cenk SÖKMENSÜER; Meral ÇALGÜNER; Yusuf BAYRAKTAR (Turkish Journal of Gastroenterology, 2019)
-